Attenuation of the virulence of a recombinant influenza virus expressing the naturally truncated NS gene from an H3N8 equine influenza virus in mice. (December 2016) - Na, Woonsung; Lyoo, Kwang-Soo; Yoon, Sun-Woo; Yeom, Minjoo; Kang, Bokyu; Moon, Hyoungjoon; Kim, Hye; Jeong, Dae; Kim, Jeong-Ki; Song, Daesub
Abstract Equine influenza virus (EIV) causes a highly contagious disease in horses and other equids. Recently, we isolated an H3N8 EIV (A/equine/Kyonggi/SA1/2011) from a domestic horse in South Korea that exhibited symptoms of respiratory disease, and found that the EIV strain contained a naturally mutated NS gene segment encoding a truncated NS1 protein. In order to determine whether there was an association between the NS gene truncation and viral virulence, a reverse genetics system was applied to generate various NS gene recombinant viruses using the backbone of the H1N1 A/Puerto Rico/8/1934 (PR/8) virus. In a mouse model, the recombinant PR/8 virus containing the mutated NS gene of the Korean H3N8 EIV strain showed a dramatically reduced virulence: it induced no weight loss, no clinical signs and no histopathological lesions. However, the mice infected with the recombinant viruses with NS genes of PR/8 and H3N8 A/equine/2/Miami/1963 showed severe clinical signs including significant weight loss and 100% mortality. In addition, the levels of the pro-inflammatory cytokines; IL-6, CCL5, and IFN-γ, in the lungs of mice infected with the recombinant viruses expressing a full-length NS1 were significantly higher than those of mice infected with the virus with the NS gene from the Korean H3N8 EIV strain. In this study, our results suggest that the C-terminal moiety of NS1 contains a number of virulence determinants and might be a suitable target for the development of a vaccine candidate against equine influenza.